Anti-Inflammatory Activity of Diterpenoids from Celastrus orbiculatus in Lipopolysaccharide-Stimulated RAW264.7 Cells - Hyun-Jae Jang; Kang-Hoon Kim; Eun-Jae Park; Jeong A. Kang; Bong-Sik Yun; Seung-Jae Lee; Chan Sun Park; Soyoung Lee; Seung Woong Lee; Mun-Chual Rho (Journal of Immunology Research)
Celastrus orbiculatus Thunb has been known as an ethnopharmacological medicinal plant for antitumor, anti-inflammatory, and analgesic effects. Although various pharmacological studies of C. orbiculatus extract has been reported, an anti-inflammatory mechanism study of their phytochemical constituents has not been fully elucidated. In this study, compounds 1–17, including undescribed podocarpane-type trinorditerpenoid (3), were purified from C. orbiculatus and their chemical structure were determined by high-resolution electrospray ionization mass (HRESIMS) and nuclear magnetic resonance (NMR) spectroscopic data. To investigate the anti-inflammatory activity of compounds 1–17, nitric oxide (NO) secretion was evaluated in LPS-treated murine macrophages, RAW264.7 cells. Among compounds 1–17, deoxynimbidiol (1) and new trinorditerpenoid (3) showed the most potent inhibitory effects (IC50: 4.9 and 12.6 μM, respectively) on lipopolysaccharide- (LPS-) stimulated NO releases as well as proinflammatory mediators, such as inducible nitric oxide (iNOS), cyclooxygenase- (COX-) 2, interleukin- (IL-) 1β, IL-6, and tumor necrosis factor- (TNF-) α. Its inhibitory activity of proinflammatory mediators is contributed by suppressing the activation of nuclear transcription factor- (NF-) κB and mitogen-activated protein kinase (MAPK) signaling cascades including p65, inhibition of NF-κB (IκB), extracellular signal-regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK), and p38. Therefore, these results demonstrated that diterpenoids 1 and 3 obtained from C. orbiculatus may be considered a potential candidate for the treatment of inflammatory diseases.